Challenges facing the early childhood development sector in South Africa - Eric Atmore (South African Journal of Childhood Education, 2012)
In this review article, the context of young children in South Africa in 2012 is described and the main challenges affecting children and the early childhood development sector (ECD) in South Africa are investigated. A situation analysis of ECD in South Africa was undertaken using South African government ECD policy and programme implementation reports. There has been progress since 1994, both quantitatively and qualitatively. The number of children in Grade R has trebled since 2001, government education and social development budgets have increased substantially and 58% of children at ECD centres nationally are now subsidised. More children are in provision and in better quality provision than before. However, much still remains to be done before we can say with confidence that the needs of our youngest children are being met. This study identifies infrastructure, nutrition, ECD programmes, teacher training, institutional capacity and funding as the major gaps in ECD provision.